1975
DOI: 10.1159/000301517
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Transport to and Survival in the Human Fallopian Tube

Abstract: A review is given on sperm migration to and sperm survival within the human Fallopian tube. Sperm migration from the external os can be very fast. The survival time of spermatozoa in the oviduct has been demonstrated to be 85 h. Spermatozoa normally enter the abdominal cavity through the open fimbriated end. Laterally closed oviducts retain spermatozoa resulting in a larger number of spermatozoa than in the normal oviduct, where the number of sperm at the site of fertilization is very low. The morphology of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(14 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, since pregnancies can result from intercourse as early as 5 days prior to ovulation, human spermatozoa must be stored somewhere in the female tract. It has been observed that spermatozoa can survive and remain fertile in the fallopian tubes for up to 85 h [39]. Spermatozoa that reach the fallopian tubes have been reported to have a higher amount of morphologically normal cells than is seen lower in the female reproductive tract [40], supporting the theory that the natural barriers sperm encounter in the female serve to select for the most viable spermatozoa capable of successfully fertilizing the oocyte.…”
Section: Fallopian Tubesmentioning
confidence: 95%
“…Nevertheless, since pregnancies can result from intercourse as early as 5 days prior to ovulation, human spermatozoa must be stored somewhere in the female tract. It has been observed that spermatozoa can survive and remain fertile in the fallopian tubes for up to 85 h [39]. Spermatozoa that reach the fallopian tubes have been reported to have a higher amount of morphologically normal cells than is seen lower in the female reproductive tract [40], supporting the theory that the natural barriers sperm encounter in the female serve to select for the most viable spermatozoa capable of successfully fertilizing the oocyte.…”
Section: Fallopian Tubesmentioning
confidence: 95%
“…Although the estimated time of ovulation might have been in error, it is likely that at least 72 h elapsed between insemination and ovulation. Ahlgren (1975) observed motile spermatozoa in the tubai ampulla 85 h after coitus. However, there is no evidence that these spermatozoa retained their ability to fertilize.…”
Section: Physiological Functionsmentioning
confidence: 95%
“…Several studies have documented that sperm can be retrieved from the fallopian tubes within 5 minutes to 2 hours after insemination of semen in the vagina (Kesseru et al 1974;Kunz et al 1996;Settlage, Motoshima, and Tredway 1973;Ahlgren 1975). Kunz et al note that spermatozoa are directed preferentially into the tube ipsilateral to the dominant follicle, thereby suggesting that there will be a preferential accumulation at the site of fertilization (Kunz et al 1996).…”
Section: Cervical Mucus Effects Sperm Transport and Capacity To Fermentioning
confidence: 99%